Thermal enhancing effect of upconversion luminescence in Er3+/Yb3+ co-doped Cs3BiSr(P2O7)2 phosphors. Issue 32 (29th July 2022) - Cui, Hongqiang; Cao, Yongze; Zhang, Yuhang; Li, Lei; Li, Guojian; Xu, Sai; Wang, Yichao; Zhang, Jinsu; Chen, Baojiu
Abstract : Cs3 BiSr(P2 O7 )2 :Er 3+ /Yb 3+ phosphors show excellent upconversion luminescence thermal enhancement performance under 980 nm (a) and 1550 nm (b) laser excitation, respectively. Abstract : A series of Er 3+ /Yb 3+ co-doped Cs3 BiSr(P2 O7 )2 (CBSPO) phosphors with significant thermal enhancement were successfully prepared using the solid-state method and the thermal-enhancing effect was studied in detail. When the temperature increased from 303 to 723 K, the upconversion luminescence (UCL) emission intensities of 2 H11/2 → 4 I15/2 and 2 H11/2 + 4 S3/2 → 4 I15/2 of Er 3+ in CBSPO:0.1Er 3+ /0.2Yb 3+ were enhanced 22.81 and 10.06 times under 980 nm laser excitation, respectively. Meanwhile, the UCL color of the sample obviously changed from orange to green with the increase in temperature. Furthermore, the UCL thermal enhancement mechanism was demonstrated, which originates from phonon-assisted transitions. In addition, the maximum absolute temperature sensitivity for CBSPO:0.1Er 3+ /0.2Yb 3+ was calculated to be 0.01026 K −1 at 563 K via luminescence intensity ratio (LIR) technology. All the results show that the CBSPO:Er 3+ /Yb 3+ phosphors can be used for safety warning and temperature measurement at high temperatures.